E-141 Large vessel occlusion stroke thrombectomy in the elderly: is 90 the new 80?. (22nd July 2019) - Bouslama, M; Rodrigues, G; Pisani, L; Haussen, D; Frankel, M; Nogueira, R
Abstract : Background: Little is known on the outcomes of nonagenarians treated with endovascular therapy (ET) for acute large vessel occlusion stroke. It remains unclear whether they have worse clinical outcomes than octogenarians. Methods: We reviewed our prospectively collected endovascular database at a tertiary care academic institution between 09/2010–11/2018. All patients older than 80 years that underwent endovascular therapy for large vessel occlusion anterior circulation acute ischemic stroke were included and categorized into two groups: 80–89 years (octogenarians), and 90–99 years(nonagenarians). Baseline, procedural, and radiological characteristics, as well as outcome parameters were compared. Receiver operating characteristic curves were used to calculate the optimal final infarct volume (FIV) threshold to predict good outcomes in both age category. Results: Fifty nonagenarians and 248 octogenarians were treated over the 8-year study period. When compared with octogenarians, nonagenarians were less often males (18% vs 34.8%, p=0.02) had lower rates of DM (12% vs 24.9%, p=0.047) and pre-procedure glucose levels (114[104–143] mg/dl vs 126[109–152], p=0.013). Other baseline characteristics and procedural parameters were comparable between groups. In terms of outcomes, rates of successful reperfusion (mTICI 2b-3) (92%% vs 91.9%, p=1.0) and any parenchymal hematomas (PH) (8.3% vs 13.3%, p=0.34) were comparable. There was a non-significant trend toward better 90-Day independent outcomes (mRS 0–2) and higher 90-day mortality favoring octogenarians (13.6% vs 25.3%, p=0.094 and 52.3% vs 38.7%, p=0.095 respectively) while ambulatory outcomes were more similar (mRS 0–3) (38.1% vs 41.9%, p=0.212). There was a non-significant shift in the overall distribution of 90-day mRS favoring octogenarians. In multivariate analysis, baseline NIHSS, ASPECTS, IV t-PA, Successful reperfusion (mTICI 2b-3) and any PH were independent predictors of a favorable shift in mRS while age category was not. A FIV ≤16.9 ml (sensitivity 67%, specificity 75%) in octogenarians and less than 12.8 mL (sensitivity 79%, specificity 80%) in nonagenarians demonstrated the greatest accuracy for identifying good outcomes. Conclusions: Our study shows that there were no differences in procedural and clinical outcomes between nonagenarians and octogenarians treated with ET with more than 1/3 of nonagenarians were ambulatory at 90 days. However, advanced age seems to be associated with reduced tolerance for infarct volume. Further research is needed to optimize selection modalities in this age cohort. Disclosures: M. Bouslama: None. G. Rodrigues: None. L. Pisani: None. D. Haussen: None. M. Frankel: None. R. Nogueira: 2; C; Covidien/Medtronic (SWIFT and SWIFT-PRIME Steering Committee - modest, STAR Trial Core Lab - significant), Stryker Neurovascular (Trevo-2 Trial PI - modest, DAWN Trial PI – no payment, Trevo Registry Steering Committee – no payment, Physician Advisory Board/Consultant - significant), Neuravi/Cerenovus (ARISE-II Trial Steering Committee – no payment, Physician Advisory Board - modest), Phenox (Physician Advisory Board/Consultant – modest), Genentech (Physician Advisory Board/Consultant – modest). 6; C; Penumbra (3-D Separator Trial Executive Committee – no payment).